METHODS OF DEVELOPING PHYSICAL QUALITIES - Gapparov Khafiz Zakhidovich, Hikmatilla Rakhmanberdievich Akhmedov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article provides insights into the development of physical qualities in sports, its methods and mistakes.